Suppression of stimulated rotational Raman scattering over long air paths via controlling the polarization state. (20th March 2015) - Feng, B.; Fan, X.M.; Lu, Z.W.; Lin, D.Y.; Yang, F.; Wang, Y.L.
Abstract Stimulated rotational Raman scattering (SRRS) limits the effective transmission distances of the high-energy and high-power laser pulses in laser–fusion systems and other applications. A simple and practical method of suppressing SRRS process by controlling the polarization direction of Stokes light is proposed. For a narrowband, linearly polarized, flat-topped laser pulse of 351 nm with intensity of 2 GW/cm2 and width of 3 ns, the SRRS threshold distance in air is lengthened to 30.0 m from 16.2 m easily using the method. Simulation results demonstrate that the method is also applicable for broadband laser.